Lung cancer patients with chronic obstructive pulmonary disease benefit from anti-PD-1/PD-L1 therapy - Lin, Mao; Huang, Zongyao; Chen, Yingfu; Xiao, Hongtao; Wang, Ting (Frontiers in Immunology, 2022)
Lung cancer (LC) and chronic obstructive pulmonary disease (COPD) are two of the most fatal respiratory diseases, which seriously threaten human health and impose heavy burden on families and society. Although COPD is a significant independent risk factor for LC, it is still unclear how COPD affects the prognosis of LC patients, especially the benefits of COPD in immunotherapy. With the development of immune checkpoint inhibition (ICI) therapy, increasing inhibitors of programmed cell death-1 (PD-1) and PD-1 ligand (PD-L1) are applied to the treatment of LC. Recent studies suggest that LC patients with COPD may benefit more from immunotherapy. In this review, we systematically summarized the outcomes of LC patients with COPD after anti-PD-1/PD-L1 treatment, and discussed the tumor immune microenvironment (TIME) regulated by COPD in LC immunotherapy, which provides novel insights for the clinical treatment of LC patients with COPD.